Love bites - St. Aubin, Cynthia (Tails from the Alpha Art Gallery, 2025)
"Love Bites is the first book in a snarky supernatural mystery series with a heroine who has her priorities in order: Solve the murder, save the day, but most importantly-feed her cats. A girl's gotta eat-and so do her three cats. Recently divorced art history grad student Hanna Harvey has just fibbed her way into a job as the assistant to dangerously drool-worthy art gallery owner Mark Abernathy. For Hanna, working in the field she desperately loves provides the perfect opportunity to begin putting her life back together. Soon her cheese budget is in the black and her feline life partners are no longer eyeing her like a six-foot can of Fancy Feast. But when her boss's lady friends start turning up dead, Hanna finds herself in the crosshairs of a murder investigation. Even worse, hunky homicide detective James Morrison fears hers might be the next body he discovers. With the "help" of the gallery's quirky cast of resident artists, Hanna will have to hunt down the truth about Abernathy's dark secret-before it hunts her"-- Provided by publisher.